Investigation of Hydrogen Wear in Heavy Loaded Metal Friction Elements of Brakes - Janahmadov, A.Kh.; Skrypnyk, V.S.; Volchenko, N.A.; Yahyayeva, A.N.; Zhuravlev, D.Y.; Yevchenko, A.S. (Herald of Azerbaijan Engineering Academy, 2021)
In the materials of the article, the following issues are considered: design, operation and energy loading of friction pairs of brake devices; the difference between internal and external friction of a metallic friction element; boundary conditions in the interaction of external and internal layers of material pairs. It has been established for what reason the subsurface layer of the metal friction element has a high surface-bulk temperature. This effect is associated with the action of pulsed specific loads during electrothermomechanical friction, which "tamp" the atoms of the crystal lattices in the layer and between the layers. As a result, the layers have high electrothermal resistance, which contributes to the accumulation of thermal energy. The thickness of the electrothermal layer of the metal friction element was determined by calculation.